Lexical and Synthesis of Architectural Vernacularism of Lanting House in Banjarmasin - Mentayani, Ira; Aufa, Naimatul; Heldian, JC (ASCEE, 2022)
The cultural heritage of river life in Banjarmasin in the form of lanting houses is an important asset that can support the potential for the development of the city. One of the efforts to maintain and develop the existence of the lanting house can be done by tracing the lexicon and aspects of its vernacularism. From the historical and cultural studies of the origin of the lanting house, it was found that the culture of migrating (Lahei-Muara Teweh-Central Kalimantan) and trading culture (Hulu Sungai - South Kalimantan). To lead to a new development with new functions, the lexical